Characterization of insulin resistance in young adult survivors of childhood acute lymphoblastic leukaemia and non‐Hodgkin lymphoma. (10th April 2013) - Beauloye, Véronique; Steffens, Mélanie; Zech, Francis; Vermylen, Christiane; Maiter, Dominique
Summary Introduction An increased prevalence of metabolic disorders and cardiovascular (CV) disease has been reported in childhood acute lymphoblastic leukaemia (ALL)/non‐Hodgkin lymphoma (NHL) cancer survivors. Objective To characterize the determinants of insulin resistance (IR) observed in this population, according to the treatment received. Methods Ninety one patients (45 men, mean age: 24 ± 5 years; mean follow‐up: 15 ± 5 years) previously treated for a childhood ALL (n = 76) or NHL (n = 15) were grouped according to their previous treatment: chemotherapy only (Group I; n = 43), chemotherapy + cranial irradiation (CI) (Group II; n = 32) and chemotherapy + bone marrow transplant (BMT)/total body irradiation (TBI) (Group III, n = 16). Results A high prevalence of IR (HOMA‐S < 60%) was observed in the BMT/TBI group (88%) compared to groups I (9%) and II (16%). The IR patients from groups [I+II] (12% of these groups) showed higher BMI, fat mass (FM) and visceral fat when compared with the non‐IR patients. In contrast, the IR patients from group III had mean BMI and total FM similar to those of non‐IR patients but showed a reduction of lean body mass and an increase in the relative proportion of trunk FM similar to the IR patients from groups [I + II]. This was associated with an altered lipid profile, high TNF‐α and IL‐6 levels, and reduced adiponectin levels compared to IR patients from group [I + II] and non‐IR patients. Conclusion Childhood ALL/NHL survivors treated by BMT/TBI frequently develop severe insulin resistance associated with peripheral‐to‐central fat redistribution, rather than increased total FM, and low adiponectin levels which may contribute to their increased CV risk.